The benefit of rebon shrimp-based supplementary feeding on serum albumin level in children who have undergone stunting - Anton, Sri Sulistyawati; Bukhari, Agussalim; Baso, Aidah Juliaty A; Erika, Kadek Ayu; Anton, Anton; Warmayana, I Gede Agus Krisna (Intelektual Pustaka Media Utama, 2024)
Stunting is still an unresolved global health problem caused by inadequate nutritional intake, significantly affecting a person’s future development. Rebon-shrimp is high protein and inexpensive local food, but still underutilized. This quasi-experimental study aimed to determine the effect of supplementary feeding from Rebon-shrimp on serum albumin levels in stunting children aged 24-60 months. The intervention group (n=44) received rebon shrimp-based supplementary food for 90 days, while the control group (n=44) received a placebo. Measurement of serum albumin was carried out by the ELISA method using blood samples. The results showed a statistical difference (p<0.001) in serum albumin levels in the intervention group, while the control group did not differ statistically (p=0.363). The intervention group experienced an increase in albumin levels of 15.55 g/L, while the control group tended to experience a decrease in serum albumin levels of -1.92 g/L. There was no significant difference in serum albumin levels before the intervention in the two groups (p=0.180). Still, after the administration of rebon products, there was a significant difference in serum albumin levels between the two groups (p<0.001). Supplementary food made from rebon shrimp was beneficial for increasing the serum albumin level of stunting children.